1999
DOI: 10.1080/01140671.1999.9514103
|View full text |Cite
|
Sign up to set email alerts
|

Phenological development of chickpeas(Cicer arietinum)in Canterbury, New Zealand

Abstract: The phenological development of one variety of chickpea (Cicer arietinum L. 'Hernandez') was studied in Canterbury, New Zealand using eight sowing dates in 1992-93 (July and September), 1993-94 (July until November), and 1994-95 (October). The duration of all phases was predicted based on thermal time above 4°C. For emergence to flowering (E-F), photoperiod-corrected thermal time with a base photoperiod of 10 h was calculated, but thermal time gave a better relationship with flowering rate. The mean accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…The accessions flowered earlier under long days and higher temperature than under short days and lower temperature. Similar findings were reported by Roberts et al (1985) and Verghis et al (1999) who reported earlier flowering under 15°C than 10°C. Sethi et al (1981) reported that chickpea flowered earlier under a combination of long days with a temperature regime of 30 and 18° than short days combined with similar temperature regime.…”
Section: Discussionsupporting
confidence: 91%
“…The accessions flowered earlier under long days and higher temperature than under short days and lower temperature. Similar findings were reported by Roberts et al (1985) and Verghis et al (1999) who reported earlier flowering under 15°C than 10°C. Sethi et al (1981) reported that chickpea flowered earlier under a combination of long days with a temperature regime of 30 and 18° than short days combined with similar temperature regime.…”
Section: Discussionsupporting
confidence: 91%
“…Scholberg et al (2000), Brown and Moot (2004) established that node appearance is influenced by temperature and it is generally related to the accumulation of degree days or thermal time. Likewise, in other studies on cotton, lucerne, melon, pea and soy among others, Ellis et al (1995), Roche et al (1998); Verghis et al (1999), Baker and Reddy (2001); Moot et al (2001), Reddy and Pachepsky (2002), Brown and Moot (2004) and Setiyono et al (2005) found that phenological development, in addition to being influenced by temperature, may interact with solar radiation, age of the plant, source-sink relationships, and photoperiod duration.…”
Section: Introductionmentioning
confidence: 74%
“…Particularly, the yields of chickpea waterlogged during the vegetative stage decreased by 35 % compared to non‐stressed yields (Cowie et al ., 1996). As a result, the crop did not reach its maximum yield potential expected during the summer months (Flenet et al ., 1996; Verghis et al ., 1999). In addition, because of the use of wide 75 cm row spacing in our study, the chickpea stand density was sub‐optimal and significantly decreased total grain yield compared to the yield of chickpea grown at a conventional row spacing of 15–30 cm.…”
Section: Discussionmentioning
confidence: 99%